Kritik Filsafat terhadap Konsep dan Konteks Pendidikan Islam - Sunardji Dahri Tiam (Universitas Negeri Malang, 2016)
Human opinion, practical attitude, emotion, and egoism have dominant effects upon the actualization of a basic concept. To anticipate the probable changes or deviations, one needs to contemplate or review the basic concept and context of Islamic education from the most essential point of view, i.e. ontological and axiological point of view. By applying a descriptive-comparative method, critical-historical analysis, and reflective-inductive-deductive thinking, we will be able to discover a new ontological and axiological systesis and view about Islamic education that can bring us to the understanding of the philosophy of Islam.